1997
DOI: 10.1118/1.597967
|View full text |Cite
|
Sign up to set email alerts
|

A model for the lateral penumbra in water of a 200‐MeV proton beam devoted to clinical applications

Abstract: An experimental approach for modeling the lateral penumbra of a proton beam has been investigated. Measurements were made with a silicon diode in a water tank. Several geometrical configurations (phantom position, collimator-to-surface distance, collimator diameter, bolus thickness, air gap, etc.) and beam characteristics (range, modulation, etc.) have been studied. The results show that the lateral penumbra is almost independent of the beam modulation and the diameter of the collimator. The use of scaled vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…The fact that the source‐to‐isocenter distance (220 cm) is much smaller in the PBS nozzle than in the passive beamline used in previous studies requires a new collimator design in order to account for the greater beam divergence and any impact on the penumbra size or homogeneity of lateral dose distributions. Indeed, a smaller lateral penumbra can be obtained by using divergent collimators when they are designed to fit the beam divergence as a function of the virtual source‐axis and collimator‐axis distances . In order to take these effects into account, a divergent collimator in which the slit tilt follows the beam divergence was considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the source‐to‐isocenter distance (220 cm) is much smaller in the PBS nozzle than in the passive beamline used in previous studies requires a new collimator design in order to account for the greater beam divergence and any impact on the penumbra size or homogeneity of lateral dose distributions. Indeed, a smaller lateral penumbra can be obtained by using divergent collimators when they are designed to fit the beam divergence as a function of the virtual source‐axis and collimator‐axis distances . In order to take these effects into account, a divergent collimator in which the slit tilt follows the beam divergence was considered.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a smaller lateral penumbra can be obtained by using divergent collimators when they are designed to fit the beam divergence as a function of the virtual source-axis and collimator-axis distances. 33,34 In order to take these effects into account, a divergent collimator in which the slit tilt follows the beam divergence was considered. A 6.5-cm-thick brass multislit collimator with five slits with a width of 2 cm 9 400 lm and a center-to-center distance of 4 mm was finally manufactured and tested at our institution.…”
Section: B Collimator Designmentioning
confidence: 99%
“…The slope of this dose decrease is characterized by the transverse penumbra given by the distance to decrease between two specified dose values. In the case of lateral spreading by scattering, this distance is determined primarily by the distance between the aperture and the patient while, for scanned beams, it is primarily determined by the size of the scanned beam spot, focused at the target . In the latter case, the beam spot is normally in the shape of a Gaussian, and the conformity of the irradiated field will be related to the overall size of that beam …”
Section: Current State: Beam Delivery Systemsmentioning
confidence: 99%
“…A sharp lateral penumbra is particularly important for the treatment sites that have organs at risk (OARs) abutting the target volume. Several groups [1][2][3][4][5] have performed the measurements and Monte Carlo simulation investigating the dependency of lateral penumbra of proton beams on different beam conditions and geometrical configurations, and it was found that lateral penumbra increases with an increase in range (or energy), depth, and air gap between the aperture/range compensator and phantom.…”
Section: Introductionmentioning
confidence: 99%